Opioidergic tuning of social attachment: reciprocal relationship between social deprivation and opioid abuse - Galiza Soares, Julia A.; Sutley-Koury, Samantha N.; Pomrenze, Matthew B.; Tucciarone, Jason M. (Frontiers in Neuroanatomy, 2025)
Individuals misusing opioids often report heightened feelings of loneliness and decreased ability to maintain social connections. This disruption in social functioning further promotes addiction, creating a cycle in which increasing isolation drives drug use. Social factors also appear to impact susceptibility and progression of opioid dependence. In particular, increasing evidence suggests that poor early social bond formation and social environments may increase the risk of opioid abuse later in life. The brain opioid theory of social attachment suggests that endogenous opioids are key to forming and sustaining social bonds. Growing literature describes the opioid system as a powerful modulator of social separation distress and attachment formation in rodents and primates. In this framework, disruptions in opioidergic signaling due to opioid abuse may mediate social reward processing and behavior. While changes in endogenous opioid peptides and receptors have been reported in these early-life adversity models, the underlying mechanisms remain poorly understood. This review addresses the apparent bidirectional causal relationship between social deprivation and opioid addiction susceptibility, investigating the role of opioid transmission in attachment bond formation and prosocial behavior. We propose that early social deprivation disrupts the neurobiological substrates associated with opioid transmission, leading to deficits in social attachment and reinforcing addictive behaviors. By examining the literature, we discuss potential overlapping neural pathways between social isolation and opioid addiction, focusing on major reward-aversion substrates known to respond to opioids.